2017
DOI: 10.1177/1077558717718626
|View full text |Cite
|
Sign up to set email alerts
|

Provider Connectedness to Other Providers Reduces Risk of Readmission After Hospitalization for Heart Failure

Abstract: Provider interactions other than explicit care coordination, which is challenging to measure, may influence practice and outcomes. We performed a network analysis using claims data from a commercial payor. Networks were identified based on provider pairs billing outpatient care for the same patient. We compared network variables among patients who had and did not have a 30-day readmission after hospitalization for heart failure. After adjusting for comorbidities, high median provider connectedness-normalized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…39 Because many older adults who use rehabilitation services during hospitalization also use medical care after discharge, it is important to promote continuity between hospital care and community-based care to prevent readmissions. 36 However, the insurance-covered coordination with community care services were not associated with 30-day PAR in this study. As these services are currently provided only during hospitalization and not after discharge, there may be inadequate communication and information sharing between hospital staff and community care staff or long-term care staff to ensure postdischarge continuity of care.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…39 Because many older adults who use rehabilitation services during hospitalization also use medical care after discharge, it is important to promote continuity between hospital care and community-based care to prevent readmissions. 36 However, the insurance-covered coordination with community care services were not associated with 30-day PAR in this study. As these services are currently provided only during hospitalization and not after discharge, there may be inadequate communication and information sharing between hospital staff and community care staff or long-term care staff to ensure postdischarge continuity of care.…”
Section: Discussioncontrasting
confidence: 59%
“…Rehabilitation discharge instruction and coordination with community care were also not associated with 30-day PAR in our subjects. Although previous studies have indicated that improving patient self-care and coordination with other providers can reduce 30-day readmission rates in heart failure patients, 35,36 few studies have examined the effects of these services on readmissions among older patients using rehabilitation in acute care hospitals. It has also been reported that multicomponent interventions are more effective than single-component interventions in reducing shortterm readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified healthcare providers’ centrality measures at both whole-network level and the more closely working together community-level. Previous studies that assessed relations between provider centrality (degree and betweenness) and patient outcomes explored those characteristics for the entire network [24, 29,57]; however, the whole network centrality measures were not significant predictors for modeling of patient outcomes and only community-level metrics were significant for our dataset. This suggests the algorithm used in this study is able to identify smaller communities in the network that might be a better reflection of the care teams.…”
Section: Discussionmentioning
confidence: 87%
“…According to Barnet et al higher degree of providers in the network was associated with higher patient cost and utilization of services [24]. In contrast, another study identified that provider’s larger connectedness was associated with fewer adverse outcomes, and larger degree was associated with lower readmission rate after hospitalization for heart failure [57]. The present study showed that higher connectedness lowered risk of adverse events for the studied chronic conditions, which aligns with literature emphasizing the important of care collaboration and ease of dissemination of information which can positively impact the patient outcomes in chronic disease management.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study found that the density of physician collaboration networks was negatively correlated with hospitalization cost and readmission rate 17 . Another study reported an association of higher provider connectedness with better health outcomes, such as fewer hospital readmissions, among HF patients 27 . Various mechanisms may account for these results, such as better coordination of care, faster sharing of information, timely communication of and response to changes in patient clinical status, and effective delivery of services 28 .…”
Section: Discussionmentioning
confidence: 99%